Morphological Variation of The Transitional Area Between Wonosari Basin and Gunungsewu Karst - Husna Diah; Tjahyo Nugroho Adji; Eko Haryono; Junbing Pu (JURNAL GEOGRAFI, 2026)
This research investigates morphological variations in the transitional zone between the Wonosari Basin and the Gunungsewu Karst, an area where lithological heterogeneity, geological structure, and karstification processes interact to shape the landscape. Morphological and morphometric data were derived from Digital Elevation Model (DEM) interpretation, aerial photograph analysis, and field validation of dolines, valleys, and karst hills. The research results show that the transition zone is dominated by dissolution dolines, subsidence, collapses, and valley types that are generally blind valleys with orders of 0 to 3, a basin area of 2.35 km² with a ratio of 0.03, a valley density of 0.26 units/km, and a hill density of 18 units/km². These characteristics reflect the dominance of fluvial processes and indicate a relatively younger stage of karst development, known as fluviokarst. In contrast, Gunungsewu Karst shows a more developed morphology classified as polygonal or cockpit karst with a predominance of order 1 to 3 valleys, a basin area of 0.2 km² with a ratio of 1, a valley density of 0.67 units/km, and a hill density of 18 units/km². The dolines in this region are mostly solution-type with elongated and cockpit shapes, while dry valleys are the dominant type. Karst hills exhibit diverse morphologies, including conical, cone-convex, blunt, and elongated forms, complemented by minor features such as micropits, pits, shafts, and grikes. This study highlights the geomorphological significance of transitional karst evolution and provides essential insights for both theoretical advancement and sustainable management of fragile karst landscapes.